Analysis of heavy metal content in edible honeysuckle (Lonicera japonica Thunb.) from China and health risk assessment. Issue 10 (26th July 2020) - Fan, Lixia; Chen, Lu; Cui, Wenyu; Dong, Yanjie; Yuan, Xuexia; Wang, Lei; Liang, Jingyun; Zhao, Shancang
Abstract: Honeysuckle is a commonly used medicine for health care and treatment. To detect heavy metal pollution in honeysuckle from China and quantify the health risk of heavy metal via dietary intake, the Pb, Cd, Cr, As, Hg, Ni, Mn, Cu, and Zn contents in honeysuckle samples were determined by ICP-MS. The dissolution rate of heavy metals in honeysuckle was measured by decoction and soaking. The hazard quotient (HQ) and total hazard index (HI) were used to evaluate the noncarcinogenic risk of nine heavy metals in honeysuckle, and the carcinogenic risks of Cd and As were evaluated using the carcinogen risk. Cd exhibited the maximum permissive limit standard-exceeding rate (40.2%) in honeysuckle, followed by Cu (37.6%) and Pb (8.5%). As and Hg did not exceed the standard values, and Cr, Ni, Mn, and Zn had no limits. In a decoction fluid after 30 min of boiling, the transfer rates of Pb, Cd, As, Ni, Mn, Cu, and Zn ranged from 11.9% to 19.9%, whereas that of Cr was low (1.0%). In a soaking fluid, the transfer rates ranged from 17.0% to 56.9%; no transfer rate was detected for Hg in neither the decoction fluid nor the soaking fluid. In addition, the 95th percentile Rs of As and Cd in honeysuckle were 5.93 × 10 −6 and 8.12 × 10 −5, respectively. The carcinogenic risk of Cd at 56.99th percentile reached the threshold set by the World Health Organization (1.0 × 10 −5 ). The results showed that intake of Pb, Cd, Cr, As, Hg, Ni, Mn, Cu, and Zn by the human body through honeysuckle could not cause noncarcinogenic damage. The element As had no carcinogenic risk, but Cd had a carcinogenic risk to a certain extent.